Sensitivity and directionality of lipid bilayer mechanotransduction studied using a revised, highly durable membrane-based hair cell sensor. (7th May 2015) - Tamaddoni, Nima; Freeman, Eric C; Sarles, Stephen A
Abstract: A bioinspired, membrane-based hair cell sensor consists of a planar lipid bilayer formed between two lipid-coated water droplets that connect to an artificial hair. This assembly enables motion of the hair caused by mechanical stimuli to vibrate the bilayer and produce a capacitive current. In this work, the mechanoelectrical transduction mechanism and sensing performance is experimentally characterized for a more-durable, revised hair cell embodiment that includes a cantilevered hair rooted firmly in the surrounding solid substrate. Specifically, this study demonstrates that the revised membrane-based hair cell sensor produces higher time rates of change in capacitance (0.8–6.0 nF s −1 ) in response to airflow across the hair compared to the original sensor (45–60 pF s −1 ) that did not feature a cantilevered hair. The 10-fold to 100-fold increase in the time rate change of capacitance corresponds to greater membrane bending and, thus, higher sensing currents. Membranes in the revised sensor exhibit changes in area due to bending on the order of 0.2–2.0%, versus 0.02% for the original sensor. Experiments also reveal that the bilayer displays highest sensitivity to mechanical perturbations normal to the plane of the bilayer, a membrane can transduce hair motion at frequencies below the hair's characteristic frequency, and bilayers formed between polymerized hydrogel volumes exhibit a higher sensing currents than those formed between liquid aqueous volumes. Finally, measurements of sensitivity (5–35 pA m −1 s −1 ) and minimum (4.0−0.6 m s −1 ) and maximum (28−13 m s −1 ) sensing thresholds to airflow are performed for the first time, and we observe maximum electrical power (∼65 pW) in the membrane occurs for combinations of slower airflow and higher voltage. These results highlight that along with the dimensions of the hair and the compositions of the aqueous volumes, sensing performance can be tuned with applied voltage.